2014
DOI: 10.1007/s12013-014-0010-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact Analysis of Autoantibody Level and NR2 Antibody Level in Neuropsychiatric SLE Treated by Methylprednisolone Combined with MTX and DXM Intrathecal Injection

Abstract: The objective is to explore the clinical curative effects of methylprednisolone combined with MTX and DXM intrathecal injection in treating neuropsychiatric systemic lupus erythematosus (NPSLE) and its effects on autoantibody level and anti-N-methyl-D-aspartate receptor subtype NR2a/2b antibody (anti-NR2 antibody) level. Thirty six admitted NPSLE patients were treated by methylprednisolone combined with MTX and DXM intrathecal injection. Thirty six SLE patients without neuropsychiatric symptoms were selected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
5
1
Order By: Relevance
“…Recent studies commonly report that a subset of anti-dsDNA antibodies might cross-react with the N-methyl-D-aspartate receptor, induce apoptosis of hippocampal neurons, and are associated with CNS NPSLE, including cognitive disorder. 3841 However, our analysis findings oppose these trends; lower serum dsDNA positivity in NPSLE patients has been reported in previous studies. 10,21 In particular, comparing the serum and cerebrospinal fluid (CSF) anti-dsDNA antibody levels of NPSLE and non-NPSLE patients, the CSF dsDNA antibody level was higher in NPSLE patients, but the serum dsDNA antibody level was lower in non-NPSLE patients.…”
Section: Discussioncontrasting
confidence: 84%
“…Recent studies commonly report that a subset of anti-dsDNA antibodies might cross-react with the N-methyl-D-aspartate receptor, induce apoptosis of hippocampal neurons, and are associated with CNS NPSLE, including cognitive disorder. 3841 However, our analysis findings oppose these trends; lower serum dsDNA positivity in NPSLE patients has been reported in previous studies. 10,21 In particular, comparing the serum and cerebrospinal fluid (CSF) anti-dsDNA antibody levels of NPSLE and non-NPSLE patients, the CSF dsDNA antibody level was higher in NPSLE patients, but the serum dsDNA antibody level was lower in non-NPSLE patients.…”
Section: Discussioncontrasting
confidence: 84%
“…A total of 109 patients received a combination of intrathecal methotrexate and dexamethasone (one to five injections), and showed an association with a positive outcome [ 122 ]. Wang et al reported an effectiveness rate of 89 % of methylprednisolone treatment combined with intrathecal methotrexate in 36 NPSLE patients [ 123 ]. In addition to these results, intrathecal administration of methotrexate is not considered common practice and is limited to a few centers [ 38 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Despite the relatively large number of patients in this study, there was no follow-up information, and thus, the long-term influence of intrathecal treatment on NPSLE was unknown. Another small-size study included 36 NPSLE patients treated with MTX and DEX intrathecally and 36 SLE patients without neuropsychiatric symptoms as the control group, where all patients had steroid pulse treatment[ 11 ]. After treatment, 77.8% (28/36) of the NPSLE cases were in clinical remission, 11.1% (4/36) of the cases were effectively treated, and 11.1% (4/36) of the cases were invalid, with a total effective rate of 88.9%.…”
Section: Introductionmentioning
confidence: 99%